3D printing with biomaterials towards a sustainable and circular economy - Wijk, Ad van; Wijk, Iris van (IOS Press, 2015)
Additive manufacturing or 3D printing, manufacturing a product layer by layer, offers large design freedom and faster product development cycles, as well as low startup cost of production, on-demand production and local production. In principle, any product could be made by additive manufacturing.